2013
DOI: 10.1245/s10434-012-2825-1
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Subtype and Distant Recurrence after Ipsilateral Breast Tumor Recurrence

Abstract: Our study suggests that breast cancer subtype based on immunohistochemical staining predicts the outcomes of patients with IBTR. Further analyses are needed (UMIN-CTR number UMIN000008136).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 34 publications
3
15
0
Order By: Relevance
“…In our study, the 5-year DDFS rate was 74.4% in patients with late IBTR. This DDFS rate is comparable with the rates in other reports (range 68-80.3%) [6,13,16]. Therefore, it is clinically important to assess risk factors after late IBTR.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In our study, the 5-year DDFS rate was 74.4% in patients with late IBTR. This DDFS rate is comparable with the rates in other reports (range 68-80.3%) [6,13,16]. Therefore, it is clinically important to assess risk factors after late IBTR.…”
Section: Discussionsupporting
confidence: 88%
“…Several reports have demonstrated that patients with late IBTR have a better prognosis than those with early IBTR [3,4,5,6,8,9,10,11,12,13,14,15,16]. However, distant recurrence after late IBTR is not rare.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HER2 expression in ERC breast cancers characterises a dominant form of the 'luminal B' molecular subtype and, compared with ERC/HER2K (luminal A) tumours, these tumours tend to exhibit reduced disease-free survival (Ishitobi et al 2013) or increased recurrence rates (Millar et al 2009) and an approximately twofold increased adjusted risk of breast cancer mortality (Haque et al 2012).…”
Section: Introductionmentioning
confidence: 99%